2003
DOI: 10.1002/pola.10707
|View full text |Cite
|
Sign up to set email alerts
|

Homopolymerization of methyl methacrylate by novel salicylaldiminate‐nickel/methylaluminoxane catalysts obtained by oxidative addition of the chelate ligand to a nickel(0) precursor

Abstract: Salicylaldimine ligands, such as 5-nitro-N(2,6-diisopropylphenyl)salicylaldimine, 3,5-dinitro-N(2,6-diisopropylphenyl)salicylaldimine, and 3-phenyl-N(2,6-diisopropylphenyl) salicylaldimine were checked in the oxidative addition to bis(1,5-cyclooctadiene)nickel(0) to prepare, after activation by methylaluminoxane (MAO), novel nickel-based catalytic systems active in the polymerization of methyl methacrylate. The catalytic behavior of the aforementioned systems, in terms of activity, molecular weight, and polydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…For instance, the formation of enolate species in methacrylate polymerizations is made so that the insertion of olefins will not occur due to the endothermicity of the insertion step 1. Recently, novel catalytic systems were claimed to be active in the copolymerization of ethylene with methylmethacrylate without preceding blocking of the ester group 4, 5. Nevertheless, the synthesis of such terpolymer (ethylene‐ co ‐octene‐ g ‐methylmethacrylate) can be considered through the in situ polymerization of methylmethacrylate in the presence of molten copolymer ethylene‐ co ‐octene during an extrusion operation by using free radical hydrogen abstractors like peroxides 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the formation of enolate species in methacrylate polymerizations is made so that the insertion of olefins will not occur due to the endothermicity of the insertion step 1. Recently, novel catalytic systems were claimed to be active in the copolymerization of ethylene with methylmethacrylate without preceding blocking of the ester group 4, 5. Nevertheless, the synthesis of such terpolymer (ethylene‐ co ‐octene‐ g ‐methylmethacrylate) can be considered through the in situ polymerization of methylmethacrylate in the presence of molten copolymer ethylene‐ co ‐octene during an extrusion operation by using free radical hydrogen abstractors like peroxides 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, new salicylaldiminate nickel(II) complexes ( II ) were prepared by the oxidative addition of mononitro‐ and dinitro‐substituted salicylaldimine ligands into bis(1,5‐cyclooctadiene)nickel(0) [Ni(cod) 2 ] according to Scheme 8, 9 . IIa and IIb were isolated and structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Carlini et al reported a Ziegler-Natta-type bis(nitro-substituted phenoxyiminato) nickel catalysts for homopolymerization of ethylene [19,22], styrene [23], norbornene [24] and methyl methacrylate (MMA) [20,21] with the methylalumoxane (MAO) or bis(1,5-cyclooctadiene)nickel(0) as cocatalysts. Herein, we report the introduction of nitro substitutes on the ortho and para-position of the phenol of the phenoxyiminato back-bone (Chart 1), as well as the synthesis and structural characterization of their nickel complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the influence of electronic effect on catalytic activity of phenoxyiminato nickel(II) complexes [18], there have been a limited number of reports that describe the incorporation of electron drawing groups in the ligand ''back-bone" [19][20][21][22][23][24]. Carlini et al reported a Ziegler-Natta-type bis(nitro-substituted phenoxyiminato) nickel catalysts for homopolymerization of ethylene [19,22], styrene [23], norbornene [24] and methyl methacrylate (MMA) [20,21] with the methylalumoxane (MAO) or bis(1,5-cyclooctadiene)nickel(0) as cocatalysts.…”
Section: Introductionmentioning
confidence: 99%